Combined inhibition of bile salt synthesis and intestinal uptake reduces cholestatic liver damage and colonic bile salts in mice - Roni F. Kunst; Isabelle Bolt; Rychon D.J. van Dasselaar; Bart A. Nijmeijer; Ulrich Beuers; Ronald P.J. Oude Elferink; Stan F.J. van de Graaf (JHEP Reports, 2024)
Background & Aims: Intestine-restricted inhibitors of the apical sodium-dependent bile acid transporter (ASBT, or ileal bile acid transporter) are approved as treatment for several inheritable forms of cholestasis but are also associated with abdominal complaints and diarrhoea. Furthermore, blocking ASBT as a single therapeutic approach may be less effective in moderate to severe cholestasis. We hypothesised that interventions that lower hepatic bile salt synthesis in addition to intestinal bile salt uptake inhibition provide added therapeutic benefit in the treatment of cholestatic disorders. Here, we test combination therapies of intestinal ASBT inhibition together with obeticholic acid (OCA), cilofexor, and the non-tumorigenic fibroblast growth factor 15 (Fgf15)/fibroblast growth factor 19 (FGF19) analogue aldafermin in a mouse model of cholestasis. Methods: Wild-type male C57Bl6J/OlaHsd mice were fed a 0.05% 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet and received daily oral gavage with 10 mg/kg OCA, 30 mg/kg cilofexor, 10 mg/kg ASBT inhibitor (Linerixibat; ASBTi), or a combination. Alternatively, wild-type male C57Bl6J/OlaHsd mice were injected with adeno-associated virus vector serotype 8 (AAV8) to express aldafermin, to repress bile salt synthesis, or to control AAV8. During a 3-week 0.05% DDC diet, mice received daily oral gavage with 10 mg/kg ASBTi or placebo control. Results: Combination therapy of OCA, cilofexor, or aldafermin with ASBTi effectively reduced faecal bile salt excretion. Compared with ASBTi monotherapy, aldafermin + ASBTi further lowered plasma bile salt levels. Cilofexor + ASBTi and aldafermin + ASBTi treatment reduced plasma alanine transaminase and aspartate transaminase levels and fibrotic liver immunohistochemistry stainings. The reduction in inflammation and fibrogenesis in mice treated with cilofexor + ASBTi or aldafermin + ASBTi was confirmed by gene expression analysis. Conclusions: Combining pharmacological intestinal bile salt uptake inhibition with repression of bile salt synthesis may form an effective treatment strategy to reduce liver injury while dampening the ASBTi-induced colonic bile salt load. Impact and Implications: Combined treatment of intestinal ASBT inhibition with repression of bile salt synthesis by farnesoid X receptor agonism (using either obeticholic acid or cilofexor) or by expression of aldafermin ameliorates liver damage in cholestatic mice. In addition, compared with ASBT inhibitor monotherapy, combination treatments lower colonic bile salt load.